Impact of packaging shape and material on consumer expectations - Poslon, Suzana; Kovačević, Dorotea; Brozović, Maja (Journal of Graphic Engineering and Design, 2021)
Packaging appearance is important in evoking consumer impressions. No study has yet explored how two prominent packaging attributes, shape and material, affect the consumers’ impressions and their expectations in the case of coffee products. Therefore, the objective of this study was to investigate whether the packaging shape has an impact on the taste intensity expected by the consumer, and whether packaging materials influence the expected coffee quality. In an online experiment, 115 participants evaluated different packaging samples. They rated the expected taste intensity for packaging samples that varied in shape complexity (i.e., cylindrical, roundedangular, hexagonal and multifaceted). They also rated the expected coffee quality for packaging samples that varied in material (i.e., plastic, aluminium, glass and metal). The results showed that the packaging with a higher degree of shape complexity was associated with a higher taste intensity. Furthermore, we found a negative effect of glass on the expectation of product quality. The findings could be applied in product packaging design which aims to match the expected and actual characteristics of the product. Article history: Received (February 8, 2021); Revised (April 23, 2021); Accepted (May 5, 2021); Published online (June 1, 2021)